Growth inhibitory potential and anti-metastatic effect of camel urine on 4T1 cell line in vitro and in vivo - Romli, Muhammad Firdaus (2016)
Breast cancer has been a prominent health problem throughout the world,claiming thousands of lives directly or indirectly by metastasizing to distant organs of the body. Hence, researches have designed several drugs to combat breast cancer with acceptable efficacy displayed although it comes with terrible side effects and emergence of resistant strain after prolonged use of the drugs.Therefore, the public has pushed forward the need to discover new anti-cancer compound from natural extract which has similar properties as the drugs but with little or no side effect. Although it may sound disgusting,camel urine has been consumed extensively for years by the Middle Eastern as it is believed to be able to treat wide range of diseases such as fever, cold or even cancer, apparently. They usually take it by mixing small drops with camel milk or take it by itself directly. The project aims to study the effects of camel urine in inhibiting the growth potential and metastatic ability of 4T1 cancer cell line in vitro and in vivo. Based on the MTT result, the cytotoxicity of the camel urine against 4T1 cell was established and it was dose-dependent at 2mg/mL.Additionally, the anti-metastatic potential of the camel urine was tested by running several assays such as scratch assay, migration and invasion assay and mouse aortic ring assay. Those assays displayed promising result in the ability of the camel urine to inhibit metastatic process of the 4T1 cells. In order to fully establish camel urine potential, an in vivo study was carried out by treating mice inoculated with 4T1 cells with two different doses of the camel urine at 120 mg/kg and 240 mg/kg. By the end of the treatment period, the tumor size in the low dose and high dose groups have reduced in size at 1.26 ± 0.07 g and 1.16 ± 0.27 g respectively as compared to the negative control group. Additional assays such as TUNEL esay,immunophenotyping, cytokine level detection assay, clonogenic assay and proteome profiler demonstrated the capability of the camel urine to reduce and inhibit the metastatic potential of 4T1 cells in vivo. High dose treatment inhibited the formation of colonies in the lung of the mice to 12 ± 1.53 while low dose treatment clocked in 26 ± 2.31 colonies. In conclusion, camel urine is justified to be consumed as a supplement to combat cancer as evidenced through the in vitro and in vivo studies carried out as it managed to reduce the tumor size and inhibit the metastatic events in the treated groups. Apart from that, this project has laid out the mechanisms employed by the substance to inhibit the growth and the metastatic process of 4T1 cell.